Effectiveness of Group Guidance with OARS Technique in Preventing Student Brawling Behavior - Aulia, Dahlia; Syarqawi, Ahmad (Journal of Social Work and Science Education, 2025)
The increasing incidence of student brawls in various regions of Indonesia often becomes headline news in various media, both print and social media. However, in reality, not all students have knowledge about the dangers of brawling. The reality in schools shows that nearly 50% of students are still unaware of the dangers of such behavior. The purpose of this study is to explore in depth how the OARS technique, when applied in group counseling services, can significantly enhance students’ knowledge about brawl prevention. This research is categorized as quantitative and employs a pre-experimental method using a One Group Pretest-Posttest design. The subjects of the study were 32 students from class XI-8 of SMA Tamansiswa Pematangsiantar. The data analysis technique used was a non-parametric statistical test with the Wilcoxon test. Based on the results of the Wilcoxon test, an Asymp. Sig (2-tailed) value of 0.005 was obtained, indicating a statistically significant result since the value is < 0.05. Therefore, the alternative hypothesis (Ha) is accepted. From these results, it can be concluded that group counseling services using the OARS technique are effective in preventing student brawling behavior among students at SMA Tamansiswa Pematangsiantar.